Dynamic plant spacing in tomato results in high yields while mitigating the reduction in fruit quality associated with high planting densities - Karpe, Margarethe; Marcelis, Leo F. M.; Heuvelink, Ep (Frontiers in Plant Science, 2024)
High planting densities achieve high light interception and harvestable yield per area, but at the expense of product quality. This study aimed to maintain high light interception without negative impacts on fruit quality. Dwarf tomato was grown at four densities in a climate-controlled room: at two constant densities (high and low) and two dynamic spacing treatments (maintaining 90% and 75% ground coverage by decreasing planting density in 3-4 steps), respectively resulting in ~100, 19, 54, and 41 plants per m 2 averaged over 100 days of cultivation. Constantly high density resulted in highest light use efficiency (LUE; 7.7 g fruit fresh weight mol -1 photons incident on the canopy) and highest harvestable fruit yield (11.1 kg m -2 ), but lowest fruit size and quality. Constantly low density resulted in lowest LUE and yield (2.3 g mol -1 and 3.2 kg m -2 , respectively), yet higher fruit size and quality than under high density. Compared to low density, maintaining 90% ground coverage increased yield (9.1 kg m -2 ) and LUE (6.4 g mol -1 ). Maintaining 75% ground coverage resulted in 7.2 kg m -2 yield and 5.1 g mol -1 LUE. Both dynamic spacing treatments attained the same or slightly reduced fruit quality compared to low density. Total plant weight per m 2 increased with planting density and saturated under constantly high density. Assimilate shortage at the plant-level and flower abortion lowered harvestable fruit yield per plant, sweetness, and acidity under constantly high density. Harvestable fruit yield per plant was highest under dynamic spacing and low density. Under constantly high density, morphological responses to lower light availability per planti.e., higher specific leaf area, internode elongation, and increased slendernesscoincided with the improved whole-plant LUE (g plant dry weight mol -1 photons). We conclude that constantly high planting density results in highest harvestable fruit yield per area but with reduced fruit quality. Dynamic spacing during cultivation produces the same fruit quality as constantly low density but with more than doubled harvestable yield per area.